Comparative Analysis of Proteomics Biomarkers Associated with Residual Ridge Resorption Induced by Denture Wear - Ahmad, Rohana; Mohamad Napi, Ainin Sofia; Lim, Tong Wah; Tan, Su Keng; Karsani, Saiful Anuar; Mazlan, Musalmah; Teh, Lay Kek; Morgano, Steven M; Baba, Nadim Z (UI Scholars Hub, 2021)
Background: The biochemical bone turnover markers for residual ridge resorption (RRR) are unclear. Therefore, the present study aimed to determine the biochemical bone turnover markers associated with RRR by comparing proteomics between the compressed mucosa of denture wearers and the non-compressed mucosa of non-denture wearers. Methods: The mucosal specimens of 11 complete-denture wearers were obtained from the alveolar ridge during surgical implant exposure for implant-retained overdentures. All denture wearers had been edentulous and worn dentures for at least 5 years. The tissues of 11 non-denture wearers were taken from the ridge during minor preprosthetic surgery. The mucosal proteins were extracted, purified, precipitated, and subsequently separated by two-dimensional gel electrophoresis for comparative proteomics. Differentially expressed proteins between the groups were analyzed by ANOVA using Progenesis SameSpots software. Results: Comparative proteomics analysis showed significant upregulation of 78 kDa glucose-regulated protein (GRP78; +2.2 fold, p = 0.015) and lumican (+1.8 fold, p = 0.005), as well as significant downregulation of heat shock protein 27 (HSP27; −1.9 fold, p = 0.029) in the denture group. Conclusions: Differential expression of the biochemical bone turnover markers of GRP78, lumican, and HSP27 may occur as a result of denture pressure on the mucosa. These markers may play important roles in RRR.